Implementasi Pendekatan Saintifik Dalam Pembelajaran Bahasa Jawa Kelas V Di SD Negeri 1 Karanganyar - Budiono Budiono (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
Learning Javanese at SD Negeri 1 Karanganyar looks monotonous and less meaningful, resulting in low motivation and student learning outcomes. Therefore, it is necessary to apply a scientific approach in supporting the 2013 curriculum. The purpose of this research is to find out the implementation of scientific approach in learning Javanese language class SD Negeri 1 Karanganyar. The research method uses qualitative approach and phenomenological research type. Research data is obtained through interviews, observations, and documentation. Data analysis is obtained through data collection, data reduction, data presentation, and conclusion drawing. The results of this study showed that the implementation of scientific approach in Javanese language learning in fifth graders about Pangkur song through five stages, namely: observing, questioning, exploring, osciating, communicating and implications for students' learning motivation. But in the implementation of scientific approach implementation 5M is done not necessarily in order but adjusting to the situation and conditions during learning. The five stages have been implemented at SD Negeri 1 Karanganyar well and optimally and have implications for students' learning motivation is very high.